PENGARUH E-SERVICE QUALITY DAN PROMOSI PENJUALAN TIKET BIOSKOP ONLINE TERHADAP KEPUASAN PENGGUNA APLIKASI TIX ID DI PEKANBARU - Molly Dwitas Rahayu; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The TIX ID application is one of the most widely used online cinema ticket sales applications in Indonesia. As an online cinema ticket sales application, TIX ID provides quality electronic services (e-service quality) and attractive sales promotions. This research is based on the stimulus-response theory which describes communication as a simple process of action and reaction, starting with the stimulus and ending with the response. The purpose of this study was to determine how much influence e-service quality and promotion of online cinema ticket sales on user satisfaction of the TIX ID application in Pekanbaru.The research method used is explanative research with a quantitative approach. The data collection technique in this study used a questionnaire with a sample size of 100 respondents who were taken using the unknown population formula with purposive sampling and accidental sampling techniques. The data analysis method used is multiple linear regression analysis, t test, F test and coefficient of determination with the help of SPSS version 24.The results of the study were based on multiple linear regression analysis. The regression equation for the study was Y = -0,758 + 0.187 X1 + 0.477 X2. Through the t test and F test, the significance value of each test is smaller than α = 0.05. The coefficient of determination test results of 52% is in the medium category. This means that there is a considerable influence between the e-service quality of online cinema ticket sales promotions on user satisfaction of the TIX ID application in Pekanbaru. Keywords: E-Service Quality, Sales Promotion, User Satisfaction, TIX ID Application